ANALISIS FILM ARTIFICIAL INTELLIGENCE (AI) PADA ASPEK SOSIAL, KULTURAL DAN TEKNOLOGI - Luhukay, Marsefio S. (Institute of Research and Community Outreach - Petra Christian University, 2008)
Why do we have such interest in analyzing a movie? Because movie is interesting and, yet, ambiguous. On one side, a movie is rich with elements of postmodernism. On the other side, movie is filled with real representation of social realities that occurred in real world; where human unable to accept it limitation, humanity. Because, there are certain things that human should not do. Humans endured in themselves the emotions which add complexities in meeting their problems. Whilst, robots have none. Robot is efficient and as a machine it has a great power that humans do not possess. Humans desire for robots in this world, because humans need to gain control. There is a wanting for taking control on their fellow humans. If, that can be done, then there will be wars of interest, enmity, conflicts, and so on. But, if, in some way, robots are the object of control, everything will be different. Robots controlled by humans, and humans handle the remote control or the chip.